2021
DOI: 10.26444/aaem/144380
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-induced growth inhibitor 1 in alcohol-induced liver cirrhosis

Abstract: Introduction andObjective. Human oxidative stress-induced growth inhibitor 1 (OSGIN1) is a protein identified in 2001 which belongs to the OKL38 protein family. The aim of the study was to investigate the levels of this protein depending on the severity of alcohol-induced liver cirrhosis. Materials and method. The study group consisted of 60 patients: 30 patients with cirrhosis in the P-Ch A and B stage and 30 in the P-Ch C stage. The control group consisted of 18 healthy individuals without liver diseases, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…They found that OSGIN1 and FGF21 levels were elevated in people with ALC, and that levels of OSGIN1 correlated with levels of FGF21. Interestingly, OSGIN1 levels were highest in the cirrhosis group at the Child-Pugh C stage, while FGF21 levels were highest in the combined Child-Pugh A/B group compared to Child-Pugh C. 71 Another study that measured serum FGF21 levels in people with alcohol-associated hepatitis vs. people with decompensated alcohol-associated cirrhosis found elevated FGF21 levels in the hepatitis group compared to cirrhosis. 72 Together, these data indicate that acute alcohol exposure increases FGF21, and that ALD is associated with elevated FGF21 levels, which may be blunted in more severe forms of ALD in which the liver is cirrhotic and reduced overall functioning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that OSGIN1 and FGF21 levels were elevated in people with ALC, and that levels of OSGIN1 correlated with levels of FGF21. Interestingly, OSGIN1 levels were highest in the cirrhosis group at the Child-Pugh C stage, while FGF21 levels were highest in the combined Child-Pugh A/B group compared to Child-Pugh C. 71 Another study that measured serum FGF21 levels in people with alcohol-associated hepatitis vs. people with decompensated alcohol-associated cirrhosis found elevated FGF21 levels in the hepatitis group compared to cirrhosis. 72 Together, these data indicate that acute alcohol exposure increases FGF21, and that ALD is associated with elevated FGF21 levels, which may be blunted in more severe forms of ALD in which the liver is cirrhotic and reduced overall functioning.…”
Section: Resultsmentioning
confidence: 99%
“… 62 Alcohol Humans Individuals with varying degrees of alcohol-related cirrhosis using the Child-Pugh score and related categories (P-Ch A, B, and C) and Healthy Controls FGF21 levels increased in participants with liver cirrhosis compared to HC FGF21 levels were highest in P-Ch A and B grp compared to P-Ch C Sak et al. 71 Alcohol Humans People with varying degrees of ALD: alcohol-associated hepatitis vs. decompensated alcohol-associated cirrhosis groups. Serum FGF21 measured in both groups.…”
Section: Star Methodsmentioning
confidence: 99%